Design and fabrication of an extrusion teaching aid RIG / Wan Ali Wan Daud and Mohd Amijar Kadimon - Wan Daud, Wan Ali; Kadimon, Mohd Amijar (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1996)
Extrusion Machine is one of famous machine that use a factory in Malaysia. Hot Extrusion Machine is most used at factory in Malaysia. It is used primarily to manufacture semifinished products such as bars , tubes or profile sections. The main advantage over other processes ,such as rolling or bar drawing ,is that practically any desired cross-sectional shape can be produced , that is , not only solid sections but also hollow sections with differently shaped inner and outer contours where required.